Pattern of Anaemia in Systemic Lupus Erythemetosus (Sle) Patients - Mehedi, HM Hamidullah; Kabir, Sheikh Khairul; Alam, Md Syedul; Chowdhury, Md Abu Yusuf; Ullah, Enshad Ekram; Siddique, Md Abu Naser; Uddin, Mohammed Jashim; Sattar, Md Abdus; Paul, Sujat (Journal of Chittagong Medical College Teachers’ Association, 2018)
Background: Anaemia of Chronic Disease (ACD) is the most common form of anaemia in patients with Systemic Lupus Erythemetosus (SLE) Autoimmune Hemolytic Anaemia (AIHA), Iron Deficiency Anemia (IDA) drug-induced myelotoxicity, and anaemia due to chronic renal failure are also often detected. Distinctly different therapeutic approaches are required for the multiple causes of anaemia in these patients. However, the pattern of anaemia among the SLE patient of this geographical area is less studied. Aim of this study was to investigate the pattern of anaemia in patients with SLE. Materials and methods: This study was carried out on the patients who had been admitted in the Departments of Medicine, Nephrology and also from outpatient Department of Chittagong Medical College Hospital (CMCH) Chittagong. SLE patients were selected consecutively as per inclusion and exclusion criteria. Detailed history and physical examinations were performed in every patient. Necessary investigations were carried out. Hematological manifestations with regards to anaemia were scrutinized and statistically analyzed. Results: A total of 42 patients (97.62% females, mean age 27.02 ±8.63 years) were studied. All the study population was anaemic (Mean±SD of Hb was 9.14±1.84 mg/dl).ACD was most prevalent (52.4%) types of anaemia 22(52.4%), followed by IDA10(23.8%), AIHA6 (14.3%) and 4(9.5%) of total patient is undetermined cause of anemia. No significant association was found between anaemia and Disease Activity Index (SLEDAI) score, fatigue and Coombs’ positivity. No association was found between the degrees of anaemia with urine protein loss. Conclusion: Anaemia is frequently encountered in SLE. A sound conception about the relative frequency of different types associated with systemic lupus erythematosus will help the clinician to take necessary measures for the wellbeing of the patient. JCMCTA 2017 ; 28 (2) : 105-110